2019
DOI: 10.5005/jp-journals-10024-2560
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Adaptation and Fracture Resistance of Three CAD–CAM Resin Ceramics: An In vitro Study

Abstract: Aim:The internal fit and resistance to fracture of resin ceramics are to be evaluated compared to that of lithium disilicate as the control group. Materials and methods: Four groups of 20 crowns each (GC Cerasmart, Vita Enamic, Coltène Brilliant Crios, and e.max CAD) were cemented on identical metal dies. Marginal gaps were measured before cementation and load to fracture was applied after cementation, half of each group was thermodynamically aged (3,000 cycles of 5° to 55° immersion followed by 200,000 cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Conversely, a study by Azarbal et al [10], in 2017, reported that VE crowns fabricated using the CEREC milling system showed marginal adaptation superior to that of lithium disilicate crowns [10]. In this study, all the hybrid material crowns produced MG values within the clinically acceptable range [9] similar to previous studies [25,26].…”
Section: Discussionsupporting
confidence: 82%
“…Conversely, a study by Azarbal et al [10], in 2017, reported that VE crowns fabricated using the CEREC milling system showed marginal adaptation superior to that of lithium disilicate crowns [10]. In this study, all the hybrid material crowns produced MG values within the clinically acceptable range [9] similar to previous studies [25,26].…”
Section: Discussionsupporting
confidence: 82%
“…A study conducted by Altieret al (17) reported that lithium disilicate (IPS e.max CAD) posterior endocrowns exhibited higher fracture strength compared to resin nanocomposite materials such as Solidex and Grandia when subjected to axial load. Similarly, Naffah et al (19) proved that lithium disilicate and Enamic restorations had higher fracture resistance when they compared to Brilliant Crios and Cerasmart restorations.…”
Section: Discussionmentioning
confidence: 93%